Programmable logic controller design of trimming machine - 239382 Leong, Mei Ling (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2005